Nurses’ knowledge and Compliance with Universal Precautions in Hilla Teaching Hospitals - Talib M. Kudhair (Iraqi National Journal of Nursing Specialties, 2023)
Objective: To assess nurses’ knowledge and compliance with universal precautions and their relationship with some sociodemographic characteristics. Methodology: A convenience sample of (loo) nurses (males and females) were working in Hilla Teaching a:SPp’e::%Moefrj#if:;.’¥stani:,ab#’e°ne#teoTj#,d2Poa;:£a#:SuE°Sfifas[e)syejrnet:::ec:d;yDau:jrger:C:;`nesc;eudctfe°dr questiormaire based on the universal precautions (UPs) guidelines recommended by the centres for diseases control and prevention (CDC) that contains (22) items. Reliability and validity of the tool were detemined through a pilot study and a panel of 4 experts. Descriptive and inferential statistical approaches were used for data analysis. Results: The study indicated that nurses’ knowledge and compliance with UPs were unacceptable and there is a significant relationship between nurses’ knowledge and compliance with UPs and some sociodemographic characteristics. Recommendations: The study recommended that an education program can be designed, constructed and implemented to the nurses related to UPs as well as further and nationwide studies can be conducted on a large sample size of nurses.